2009
DOI: 10.1007/s11096-009-9288-x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of risk factors for developing hyperkalemia when using ACE inhibitors in cardiovascular diseases

Abstract: Cardiac patients receiving ACEIs concomitantly with potentially interacting drugs are at high risk of experiencing hyperkalemia. Old age, renal disease, hepatic disease, and receiving large number of medications are factors that may significantly increase their vulnerability towards this adverse outcome; thus, frequent monitoring is advocated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 34 publications
3
13
0
Order By: Relevance
“…Data from other observational studies regarding correlations between smoking and hyperkalemia are limited. In a prospective cohort study of 500 patients with various cardiovascular diseases but no CKD, previous smoking history posed a protective role in hyperkalemia development [24] . However, in a cross-sectional study including 1,227 CKD patients smoking did not correlate significantly with serum potassium levels [25] .…”
Section: Discussionmentioning
confidence: 99%
“…Data from other observational studies regarding correlations between smoking and hyperkalemia are limited. In a prospective cohort study of 500 patients with various cardiovascular diseases but no CKD, previous smoking history posed a protective role in hyperkalemia development [24] . However, in a cross-sectional study including 1,227 CKD patients smoking did not correlate significantly with serum potassium levels [25] .…”
Section: Discussionmentioning
confidence: 99%
“…In patients with hypertensive chronic kidney disease treated with ACE inhibitors, hyperkalemia occurs frequently if the baseline and follow-up GFR is lower than 40 mL/min/1.73 m 2 [22]. Renal disease is identified as one of the predictors of hyperkalemia secondary to ACE inhibitor drug interaction [23]. In addition, Maddirala et al [24] reported that the incidence of hyperkalemia increased with progression of the stage of chronic kidney disease in ACE inhibitor or ARB users.…”
Section: Resultsmentioning
confidence: 99%
“…Hyperkalemia and hypokalemia are both commonly seen during the management of patients with HF. The former is most commonly seen in patients on more than one of ACEi, ARB, or MRA medications, diabetes or stage 3 or higher chronic kidney disease (22,23). Hypokalemia is most often seen with combination or intravenous diuretic therapy, especially if a thiazide, such as metolazone is used as part of the regimen.…”
Section: A Note On New Therapiesmentioning
confidence: 99%